Model of conceptual framework for studio based open and distance learning (ODL): A case study on students’ emotions in the Faculty of Art and Design, Universiti Teknologi MARA, Perak Branch, Campus Seri Iskandar / Muhammad Asri Azuddin ... [et al.] - Azuddin, Muhammad Asri; Shafie, Norhaslinda; Halili, Nur Akma; Soewardikoen, Didit Widiatmoko; Anwar, Ardy Aprilian; Budiman, Arief (UiTM Press, 2023)
UiTM’s Faculty of Art and Design uses “studio-based learning.” Art and design students must participate in studio conversations about their work. Malaysia too went through the MCO due to COVID-19 and this had influenced the way the education industry was run – Open and Distance Learning was applied to almost all courses. This study will examine the Technology Acceptance Model (TAM) and Pekrun Emotions and Learning Theory to assess how art and design students felt about COVID-19-related Open and Distance Learning (ODL) studio-based courses. This study will also identify students’ emotions. The Technology Acceptance Model (TAM) was used to assess ODL studio-based students’ tech attitudes. The Pekrun Emotion and Learning Theory was used to assess Art and Design students’ technological attitudes. This study employed theoretical research to combine structured observation, questionnaires, and semi-structured interviews. The findings suggest that in studio based Open and Distance Learning (ODL) classes, the Art and Design students’ emotions should be considered prior, using technology acceptance, and after, using perceived usefulness and perceived ease of use when developing online studio learning. Technology adoption precedes technology utility and simplicity of use, according to the research. The research improves teaching and learning, especially studio learning. To better respond to students’ feelings in the future, the online class should establish a healthier teaching and learning environment.